2016
DOI: 10.3390/ijms17020106
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Atorvastatin Dose and Concomitant Use of Angiotensin-Converting Enzyme Inhibitors on Renal Function Changes over Time in Patients with Stable Coronary Artery Disease: A Prospective Observational Study

Abstract: Angiotensin-converting enzyme inhibitors (ACEI) and statins are widely used in patients with coronary artery disease (CAD). Our aim was to compare changes in glomerular filtration rate (GFR) over time in subjects with stable CAD according to atorvastatin dose and concomitant use of ACEI. We studied 78 men with stable CAD referred for an elective coronary angiography who attained the then-current guideline-recommended target level of low-density lipoproteins (LDL) cholesterol below 2.5 mmol/L in a routine fasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Some studies suggested that the combination of ACEIs/ARBs and statins may have synergic effects and produce better outcomes than their sole use in particular circumstances. For example, one study suggested that concomitant ACEI and statin use appeared to beneficially modulate changes in the glomerular filtration rate in men with stable coronary artery disease [ 3 ]. It was reported that a combination of and early treatment with statins and ACEIs/ARBs could prevent extensive inflammatory responses in patients undergoing coronary artery bypass surgery [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggested that the combination of ACEIs/ARBs and statins may have synergic effects and produce better outcomes than their sole use in particular circumstances. For example, one study suggested that concomitant ACEI and statin use appeared to beneficially modulate changes in the glomerular filtration rate in men with stable coronary artery disease [ 3 ]. It was reported that a combination of and early treatment with statins and ACEIs/ARBs could prevent extensive inflammatory responses in patients undergoing coronary artery bypass surgery [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using a combination of in vitro and in vivo approaches, it is shown that metformin may be protective against renal fibrosis via inhibition of ERK signaling [ 29 ]. The use of angiotensin-converting enzyme inhibitors (ACEI) with atorvastatin may be renoprotective in male patients with coronary artery disease, assessed by GFR [ 30 ]. Finally, the role of mTOR inhibitors as therapeutic agents for the treatment of non-clear cell renal cell carcinoma, diabetic nephropathy and renal transplantation, with emphasis on the mechanistic findings underlying the renoprotective effects, is reviewed [ 31 ].…”
mentioning
confidence: 99%